Atypical Presentation of Oral Erythema Multiforme - A Case Report - Gautam, Samjhana; Limbu, Senchhema; Malla, Manisha; Dikshit, Parajeeta (Journal of Nepalese Association of Pediatric Dentistry, 2024)
Erythema multiforme (EM) is an acute, self-limiting, sometimes recurrent mucocutaneous inflammatory disorder recognized as hypersensitivity reaction primarily triggered by certain infections and drugs. It is often seen as confusing disease entity in children characterized by eruptive lesions of oral mucous membrane. Although oral involvement can occur in association with lesions of skin and other mucosal surfaces, the diagnosis is a little more challenging when the disease is completely limited to oral mucosa. Here, we report a typical case of oral EM that is confined in lip in a 7-year-old male child; with an acute onset of crusted ulcer with hemorrhagic encrustation, pain and swelling of lower lip since 2-days. Based upon patient’s detailed history of prodromal sign and symptoms, disease progression, clinical examination of wound and hematologic investigation clinical diagnosis of erythema multiforme was made. The case was treated with topical corticosteroid and topical antiviral cream for a week showcasing resolution of lesion.